Flucht und Religion Religiöse Verortungen und Deutungsprozesse von Kindern und Eltern mit Fluchterfahrungen - Konz, Britta (Verlag Julius Klinkhardt, 2021)
Based on an interdisciplinary qualitative-empirical study with Muslim, Christian and Yezidi families, this book is dedicated to the significance of religion for coping with traumatic experiences in escape processes. With the help of the concept of VulnerAbility, this book shows how the children and their parents generate agency through their faith and membership to a religious community (Belonging). In individual adaptations, they adapt their religious heritage, which is revealed in images of God and religious relevance systems, to new life contexts in a meaningful way. This allows them to develop positive visions of the future through recourse to their faith, even if they have experienced religious membership as the subject of social conflict-lines that are established in the context of origin, on the flight routes and in the German asylum system through practices of discrimination.